Learning Development Strategies Using Internet E-Learning Technology in Increasing the Learning Creativity of Class XII IPS Class Students of Senior High School Cendrawasih Makassar - AR, Sumarni; Rismawanti, Erni; Hasyim, Ahmad (ARRUS Journal of Social Sciences and Humanities, 2023)
This type of research is Classroom Action Research (PTK), which aims to increase student learning creativity in social studies class XII at Cendrawasih Makassar High School through Internet E-learning Technology with Learning Development Strategies. The subjects of this study were class XII students of SMA Cendrawasih Makassar in the odd semester of the 2022/2023 school year with a total of 25 students consisting of 14 male students and 11 female students. This research was conducted in two cycles, and each process was held in 3 meetings including a test at the end of the cycle. Data collection techniques use observation, questionnaires, and tests at the end of each cycle, and the data collected consists of quantitative and qualitative data. Based on the results of data analysis, it was obtained that the average score of student learning outcomes before the cycle was 63 percent in the low category, after the first cycle it became 74.92 percent in the medium category, then in the second cycle it increased to 86.72 percent which was in the very high category. By looking at the increased results obtained before process and after cycle I and cycle II, it can be concluded that learning development strategies with internet e-learning technology can increase the learning creativity of class XII social studies students at SMA Cendrawasih.